Memory control deficits in the sleep-deprived human brain - Marcus O. Harrington; Theodoros Karapanagiotidis; Lauryn Phillips; Jonathan Smallwood; Michael C. Anderson; Scott A. Cairney (Proceedings of the National Academy of Sciences, 2025)
Sleep disturbances are associated with intrusive memories, but the neurocognitive mechanisms underpinning this relationship are poorly understood. Here, we show that sleep deprivation disrupts prefrontal inhibition of memory retrieval, and that the overnight restoration of this inhibitory mechanism is associated with time spent in rapid eye movement (REM) sleep. The functional impairments arising from sleep deprivation are linked to a behavioral deficit in the ability to downregulate unwanted memories, and coincide with a deterioration of deliberate patterns of self-generated thought. We conclude that sleep deprivation gives rise to intrusive memories via the disruption of neural circuits governing mnemonic inhibitory control, which may rely on REM sleep.